2002
DOI: 10.1073/pnas.232573899
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activating regions target a cyclin-dependent kinase

Abstract: Several yeast activators are phosphorylated by SRB10, a cyclindependent kinase associated with the transcriptional machinery. Sites of phosphorylation are found outside the activating region in each case, and the modification has different physiological consequences in different cases. We show here that certain acidic transcriptional activating regions contact SRB10 as assayed both in vivo and in vitro. The interaction evidently positions each activator, as it activates transcription, so that it gets phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
(42 reference statements)
2
41
0
Order By: Relevance
“…18 CDK8 binds the Gal4 activation domain. 19 CDK8 promotes ATP-dependent dissociation of preinitiation complexes, resulting in a positive effect on transcription. 20 CDK8/ cyclin C phosphorylates subunits of the general transcription factor TFIID, 20 and the Mediator subunit MED2.…”
Section: Introductionmentioning
confidence: 99%
“…18 CDK8 binds the Gal4 activation domain. 19 CDK8 promotes ATP-dependent dissociation of preinitiation complexes, resulting in a positive effect on transcription. 20 CDK8/ cyclin C phosphorylates subunits of the general transcription factor TFIID, 20 and the Mediator subunit MED2.…”
Section: Introductionmentioning
confidence: 99%
“…We have applied the same techniques that we used to analyze the tup1⌬ microarrays to determine the sets of genes derepressed when the functions of Srb10 and Hda1 are disrupted. We constructed an isogenic set of strains deleted for TUP1 or HDA1 or containing a mutant of Srb10 that lacks kinase activity (srb10 D304 ) (Liao et al, 1995;Ansari et al, 2002). We also made a strain lacking both Hda1 and Srb10 functions to determine the combined effects of the two mutations on expression levels.…”
mentioning
confidence: 99%
“…In a previous article, we showed that each of an array of transcriptional acidic activating regions (yeast, mammalian, and artificial) binds Srb10 (5). The interaction, detected in vivo, was also observed in vitro with purified Srb10 alone (but not with Srb11 alone), with Srb10͞11, and with Srb10͞11 as part of the mediator complex (5).…”
mentioning
confidence: 80%
“…Gst-fused proteins were purified as described (5). Gst-fusion proteins were expressed in BL21 (DE3) pLysS bacterial strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation